Multicasting technique for path establishment in vehicular ad hoc networks - Kaur, Sukhpreet; Sharad, Er (International Journal of Engineering and Technology, 2018)
The vehicular adhoc network is the decentralized type of network in which vehicles can move from one location to another. In the network two type of communication is possible which are vehicle to vehicle and vehicle to infrastructure. In the vehicle to vehicle type of path establishment is the major issue of the network. In this research work, multicasting routing technique is proposed for the path establishment from source to destination. The proposed technique is implemented in NS2 and simulation results shows improvement in network delay for path establishmentÂ Â